TINGKAT PENGETAHUAN DAN KEJADIAN ANEMIA PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS TANJUNG KEMUNING KABUPATEN KAUR - Santoso Ujang Effendi; Buyung Keraman; Andrek Sarnandes (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2017)
The impact of the incidence of anemia in pregnant women who have less knowledge during pregnancy are abortion, preterm labor, fetal and uterine disorders, low birth weight (LBW), and high maternal mortality. This study aimed to study the relationship between the level of knowledge with the incidence of anemia in pregnant women at Tanjung Kemuning Community Health Center Kaur District. This type of research was Descriptive Correlation and the design used was Cross Sectional. The data in this study used the primary data obtained by distributing questionnaires. The population in this study was all pregnant women who checked pregnancy and did not check their pregnancy at Tanjung Kemuning Community Health Center of Kaur Regency from January to June 2016 as many as 66 pregnant women. Sampling technique are Total Sampling and obtained sampel counted 35 respondents. Data analysis was done by univariate and bivariate analysis with Chi-Square test and to know closeness using Contingency Coefficient (χ2) statistic test. The result of the research showed that there were 14 respondents (40.0%) of good knowledge, and 19 respondents (54,3%) did not experience anemia. There was a significant relationship between knowledge with the incidence of anemia in pregnant women in working area of Tanjung Kemuning Community Health Center Kaur District with a close category. Suggestion for Tanjung Kemuning Community Health Center Kaur District to increase the intake of iron nutrition in pregnant women by doing health promotion about anemia and giving iron tablets to pregnant woman. Keywords : anemia, knowledge, pregnant women